Viral genomes : diversity, properties, and parameters - Feng, Zhi, 1963-; Long, Ming (Nova Biomedical Books, 2009)
"This book describes the seven different classification of viruses, including their effects on common human diseases (i.e., common cold, chicken pox) as well as the more serious diseases (AIDS, avian influenza and SARS). The nature of the human T-cell leukemia virus type 1 (HTLV-1), the first human retrovirus and the etiologic agent of neoplastic disease, adult T-cell leukemia (ATL) is explored, as well as its effect on several inflammatory diseases. Since 1997, great concern aroused that the Asian highly pathogenic avian influenza (HPAI) H5N1 virus might turn into a pandemic strain. Thus, the enigmatic nature of the HPAI H5N1 influenza virus is also discussed. An attempt is made to identify and to characterize, qualitatively, various concrete factors that may readily become or propel critical masses. Furthermore, giant viruses, which are ancient double-stranded DNA viruses that infect a wide range of host organisms are addressed. This book also highlights current information regarding the replication, transcription, and roles of proteins of coronaviruses, viruses which are known to infect a wide range of mammalian and bird species."--Publisher's description